Enhanced glutathione production by bifunctional enzyme coupling with ydaO-based ATP regulating system in Escherichia coli. (December 2020) - Chen, Yawei; Cao, Yiting; Kong, Weizhen; Shi, Yiying; Cheng, Wanqing
Graphical abstract: Highlights: The strategy based on yda O motif and polyphosphate kinase improves GSH production. The strategy could dynamically control and stabilize ATP level at 0.20 mg L −1 OD −1 . The strategy can be used to promote the production of other ATP-driven metabolites. Abstract: Glutathione is a tri-peptide consisting of L-glutamic acid, L-cysteine and glycine, widely applied to the pharmaceutical, food, and cosmetic industries. Also, GSH has potential application in the bioremediation of soil and water. A novel ATP regulating strategy based on the ATP-sensing riboswitch yda O and polyphosphate kinase was developed. Besides, GshF from Streptococcus thermophile was introduced into the Escherichia coli BL 21. The GSH titer of the strain AYPGS(harboring pRSFDuet- yda O- ppk - gsh F) could reach 145.32 mg L −1 after 18 h fermentation, which was three times higher than that of the control and 37% higher than that of the strain AGP(harboring pRSFDuet- ppk - gsh F). The results showed that S. thermophiles -derived GshF was insensitive to feedback inhibition caused by GSH and could greatly increase the GSH production. It also proved that the ATP regulating strategy could dynamically control the ATP level and enhance GSH production. Our proposed ATP regulating strategy will be potentially applicable for other ATP-driven metabolites.